2005
DOI: 10.1002/uog.1895
|View full text |Cite
|
Sign up to set email alerts
|

Increased uterine artery vascular impedance is related to adverse outcome of pregnancy but is present in only one‐third of late third‐trimester pre‐eclamptic women

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 23 publications
5
48
2
Order By: Relevance
“…Caesarean section was reportedly less in number in comparison with vaginal delivery and fetal distress eas the main indication for caesarean section. These findings are comparable with the findings of study done by Rai L et al and Garcia B et al 12,13 Mean birth weight in present study was 2150 gm but these findings are not comparable with similar study done by Wald RM et al, Garcia B at al, Peixoto et al and Li H et al 6,11,12,14 Oligohydramnios, SFGR, Pre-eclamsia, Anemia are the most common pregnancy complications respectively.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Caesarean section was reportedly less in number in comparison with vaginal delivery and fetal distress eas the main indication for caesarean section. These findings are comparable with the findings of study done by Rai L et al and Garcia B et al 12,13 Mean birth weight in present study was 2150 gm but these findings are not comparable with similar study done by Wald RM et al, Garcia B at al, Peixoto et al and Li H et al 6,11,12,14 Oligohydramnios, SFGR, Pre-eclamsia, Anemia are the most common pregnancy complications respectively.…”
Section: Discussionsupporting
confidence: 69%
“…15 This is in contrast to the findings of Ghosh et al where RI and PI were considered better indicators of vascular impedance in predicting adverse perinatal outcomes. 16 B/L notch in uterine artery Doppler was present in 25.4% participants and this findings are quit comparable with the similar study done by Wald RM et al, Rai L et al but not consistent with study done by Maria AL et al and Li H et al 11,13,14,17 Study found acceptable sensitivity, specificity, PPV and NPV of Doppler ultrasound during third trimester to predict obstetrical and perinatal outcome and this findings are comparable with study done by Rai L et al 13 Limitations of this study was number of cases has been small and study not included Patients who came in labor or with a complication like abruptio placenta.…”
Section: Discussioncontrasting
confidence: 53%
“…Previous studies examining uterine artery PI [29,30,31,32,33] and serum PlGF or the sFlt-1 to PlGF ratio [34,35,36,37,38,39] in the late second or early third trimesters of pregnancy have essentially focused on the investigation of women presenting to specialist clinics with signs of hypertensive disorders with the aim of identifying the subgroup that will develop severe disease [29,30,31,32,33,34]. Our study examined the application of biomarkers in routine screening for subsequent development of PE as part of a strategy for a new approach to prenatal care [7].…”
Section: Discussionmentioning
confidence: 99%
“…This is in keeping with other studies showing a high incidence of Prognostic value of placental insufficiency indicators L Geerts and HJ Odendaal increased uterine artery PI before the onset of pre-eclampsia as well as in established disease, more so in severe early-onset pre-eclampsia (as in this cohort) compared to milder forms near term. 36,37 Abnormal uterine artery waveforms are strongly associated with histological abnormalities in the placenta 23,38 (that is decidual vasculopathy, accelerated villous maturation, ischemic-thrombotic lesions and infarctions) that correlate with ultrasound characteristics 23 and occur more frequently at earlier GA. 29 This is in keeping with the current findings: only 49% of placentas had a normal appearance on ultrasound and with a jelly-like placenta the pregnancies were approximately 1 week less advanced (207.3±9.9 versus 215.5±13.2 days).…”
Section: Uterine Artery Waveformsmentioning
confidence: 99%